2010
DOI: 10.1007/s13318-010-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of vertilmicin, a novel aminoglycoside antibiotic, in rats and dogs

Abstract: The pharmacokinetics of vertilmicin was investigated in rats and dogs following intramuscular or intravenous administration of vertilmicin. Following a single administration of an intramuscular dose, serum concentrations of vertilmicin peaked at 0.63 h in rats and 0.58 h in dogs. In rats, after intravenous administration of vertilmicin at dosages of 10, 20, and 40 mg/kg, the t1/2 values for vertilmicin were 0.81, 0.76, and 0.86 h, respectively, while after intramuscular administration of vertilmicin at dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…It is currently in the initial stages of clinical development. Several pharmacokinetic studies have been reported in rats [9][10][11], dogs [11] and humans [12], demonstrating that vertilmicin has similar characteristics to other aminoglycosides, including a rather short half-life. In vitro and in vivo pharmacodynamic studies revealed that the antibacterial potency of vertilmicin was higher than that of verdamicin and gentamicin [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is currently in the initial stages of clinical development. Several pharmacokinetic studies have been reported in rats [9][10][11], dogs [11] and humans [12], demonstrating that vertilmicin has similar characteristics to other aminoglycosides, including a rather short half-life. In vitro and in vivo pharmacodynamic studies revealed that the antibacterial potency of vertilmicin was higher than that of verdamicin and gentamicin [8,13].…”
Section: Introductionmentioning
confidence: 99%